Quantitative Structure-Pharmacokinetic Relationship Modelling on Quinolone Drugs: Serum Protein Binding - PAUL, YASH; S. DHAKE, AVINASH; SINGH, BHUPINDER (Asian Journal of Chemistry, 2010)
This study was conducted to investigate quantitative structure pharmacokinetic relationships (QSPR) for serum protein binding (% SPB) in humans amongst 28 quinolone drugs employing extra thermodynamic multilinear regressions analysis (MLRA) approaches. The overall predictability was found to be quite high (R2 = 0.8699, F = 19.10, S2 = 93.79, Q2 = 0.6675, p < 0.001).